Spatially resolved collective excitations of nano-plasmas via molecular dynamics simulations and fluid dynamics - Raitza, T.; Reinholz, H.; Reinhard, Paul-Gerhard; Röpke, G.; Broda, I. (New Journal of Physics, 2012)
Collective excitations in nano-plasmas are described by dynamical bi-local auto-correlation functions. These excitations, which are related to the plasmon excitations in bulk plasmas, arise in the classical as well as the quantum regime. Instead of the wave-vector-dependent dynamical structure factor, which is not well defined in finite systems, two different signatures are considered to characterize collective excitations: the bi-local particle density correlation function and the bi-local current density correlation function. The relation between both signatures is not as trivial as in the homogeneous case and is given here. Exemplary calculations are performed for expanding nearly spherical clusters of sodium atoms after excitation by a high-intensity short pulse laser beam. The lowest collective excitations obtained in the classical regime using molecular dynamics simulations agree well with the lowest collective excitations obtained from quantum calculations using fluid dynamics. The energy, damping and structure of the lowest collective modes are given. The dynamical bi-local correlation functions are of relevance for the optical properties, in particular the determination of photo absorption coefficients of nano-plasmas. © IOP Publishing and Deutsche Physikalische Gesellschaft.
CRIS-Team Scopus Importer:2023-07-24